2015
DOI: 10.1002/ejic.201500034
|View full text |Cite
|
Sign up to set email alerts
|

The Electrically Wired Molybdenum Domain of Human Sulfite Oxidase is Bioelectrocatalytically Active

Abstract: We report electron transfer between the catalytic molybdenum cofactor (Moco) domain of human sulfite oxidase (hSO) and electrodes through a poly(vinylpyridine)-bound [osmium(N,NЈ-methyl-2,2Ј-biimidazole) 3 ] 2+/3+ complex as the electron-transfer mediator. The biocatalyst was immobilized in this low-potential redox polymer on a carbon electrode. Upon the addition of sulfite to the immobilized separate Moco domain, the generation of a significant catalytic current demonstrated that the catalytic center is effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These steps involve a repositioning of the domains to reduce electron transfer distances permitting electron transfer from Mo to Fe of SO‐HD and to cytochrome c . A reaction with soluble and polymer bound redox mediators is also possible . Direct unmediated electron transfer from the reduced enzyme to electrodes proceeds via the heme domain .…”
Section: Introductionmentioning
confidence: 99%
“…These steps involve a repositioning of the domains to reduce electron transfer distances permitting electron transfer from Mo to Fe of SO‐HD and to cytochrome c . A reaction with soluble and polymer bound redox mediators is also possible . Direct unmediated electron transfer from the reduced enzyme to electrodes proceeds via the heme domain .…”
Section: Introductionmentioning
confidence: 99%
“…This reinforces the point that the negatively charged heme domain of holo HSO is more strongly attracted to the positively charged [Fe(dtne)] 3+ mediator and this enhances the catalytic response by facilitating effective electron transfer and lowering the catalytic potential. A similar observation reported for the catalytic voltammetry of holo and heme‐free HSOs with a positively charged osmium complex at a carbon electrode found that the catalytic response of heme‐free HSO was only 30% relative to that from holo HSO …”
Section: Resultsmentioning
confidence: 99%
“…Apparent Michaels constants ( K M,sulfite ) of 747 μM and 676 μM were obtained from the Michaelis–Menten plot (current taken at +480 mV) for holo HSO and heme‐free HSO electrodes, respectively (Supporting Information, Figure S4). The observed K m value is almost same at holo and heme‐free HSO electrodes and it is consistent with a recent report on electrochemistry of HSO with the polymeric positively charged mediator poly(vinylpyridine)‐[osmium‐(N,N′‐methyl‐2,2′‐biimidazole) 3 ] 3+/2+ , which found an apparent K M value of 500 and 450 μM for heme‐free and Holo HSO, respectively. Conversely, the observed K M value is very high compared to the value reported from solution assay ( K m =9 μM) for holo HSO with its physiological electron acceptor cytochrome c .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,44 Graphite electrodes have been used for the immobilization of hSO. 23,44,45 However, there are no reports on employing graphene to achieve DET between hSO and the electrodes.…”
Section: Introductionmentioning
confidence: 99%